Determinants of food producers’ intentions to obtain halal certification: An integrated TPB–halal model in Bali, Indonesia - Niswa, Harisatun; Diana, Ilfi Nur; Yuliana, Indah (Universitas Islam Indonesia, 2026)
IntroductionHalal certification has become increasingly important for food producers operating in non-Muslim-majority destinations such as Bali, where Muslim tourism continues to expand. Although numerous studies investigate halal consumption behavior, research examining producers’ intentions to obtain halal certification remains limited. This study extends existing knowledge by integrating halal knowledge and halal awareness into the Theory of Planned Behavior to explain certification intentions among food-sector entrepreneurs.ObjectivesThe study aims to identify and analyze the determinants influencing food producers’ intentions to obtain halal certification in Bali by assessing the roles of attitude, subjective norms, perceived behavioral control, halal knowledge, and halal awareness within an integrated behavioral framework.MethodA quantitative research design was employed, involving 150 food producers selected using non-probability sampling. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. Measurement and structural models were assessed to evaluate validity, reliability, and the significance of hypothesized relationships.ResultsThe findings show that all five determinants—attitude, subjective norms, perceived behavioral control, halal knowledge, and halal awareness—positively and significantly affect producers’ intentions to obtain halal certification. The model explains 85.9 percent of the variance in intention, demonstrating strong predictive power. The results highlight the combined influence of cognitive, social, and religious factors in shaping certification decisions.ImplicationsThe study provides theoretical contributions by expanding the Theory of Planned Behavior with halal-specific constructs and offers practical insights for policymakers, certification bodies, and industry stakeholders in promoting halal certification through education, technical assistance, and supportive regulatory frameworks.Originality/NoveltyThis research provides a comprehensive behavioral model for understanding halal certification intentions in a minority-Muslim tourism context, offering new insights into how halal knowledge and awareness strengthen producers’ decisions to pursue formal certification.